Isolation and Molecular Characterization of Abiotic Stress Tolerant Plant Growth Promoting Pseudomonas spp. from Different Rhizospheric Soils of Telangana State, India - Damodarachari, K.; Reddy, R. Subhash; Triveni, S.; Rani, CH. V. Durga; Sreedhar, M. (International Journal of Bio-resource and Stress Management, 2018)
The present investigation was carried out to isolate rhizobacteria from different rhizospheric soils of Telangana state, India and screened for plant growth promoting properties such as mineral nutrient solubilization (P, K, Zn), IAA production, ACC deaminase, EPS production, biocontrol activity and tolerance to different abiotic stresses such as pH, temperature, salt, drought and heavy metals in vitro conditions. Based on cultural, morphological and biochemical characterization, it was found that forty four were of Pseudomonas spp. Among the forty four (44) Pseudomonas isolates, twenty eight (28) isolates were showing plant growth promoting properties. The results of different in vitro abiotic stress tolerance of Pseudomonas isolates, four isolates were showed growth at pH range from 4-10 (PS 1, PS 4, PS 26, PS 40). Five isolates were showed tolerance to 1.5 to 20% of NaCl concentration (PS 4, PS 15, eight isolates were showed tolerance from 1.5 to 15% of NaCl concentration (PS 1, PS 11, PS 18, PS 26, PS 30, PS 31, PS 32, PS 40), three isolates showed tolerance to temperature from 20 °C -50 °C (PS 11, BS 15, BS 40), nine isolates were showed tolerance to temperature from 20 °C -45 °C (PS 1, PS 4, PS 21, PS 23, PS 28, PS 30, PS 32, PS 34, PS 37), three isolates showed tolerance to water potential from -0.05 Mpa to -0.73 Mpa (PS 4, PS 15, BS 34).PS 15 was found efficient in Zn- solubilization with considerable other PGP properties. It was tolerant to pH stress (4, 6), temperature stress, salt stress, drought stress and heavy metals As and Cd only. PS 1 showed good P-solubilization, K-solubilization, Zn solubilization with biocontrol activity. It tolerated pH stress, temperature stress, salt stress, drought stress and tolerant to heavy metal toxicity. Performing environmental parameters for bacterial growth is also showing that bacteria can easy to survive in different environmental condition.